Kapitał społeczny a ład moralny we współczesnym społeczeństwie - Adamczyk, Monika (Acta Universitatis Lodziensis. Folia Sociologica, 2012)
Contemporary societies are not able to evade individualisation processes, a consequence of structural diversification of the society, increased material standard of living and access to mass consumption. Transformations occurring in today’s societies evidence a need for analysing the mechanisms of resource creation, constituting an alternative to the current order. Can social capital be treated as a moral resource participating in the development of a new social order? Created and communicated through – among others – religion and tradition, it cannot be evaluated measurably, and yet it constitutes a fundamental element of the community’s resources. Possession of those resources is particularly important in connection with the above mentioned transformations and the inclination of contemporary culture to over-emphasise man’s right to „freedom without limitations”.